Intestinal microbiome adjusts the innate immune setpoint during colonization through negative regulation of MyD88. Issue 1 (December 2018) - Koch, Bjørn; Yang, Shuxing; Lamers, Gerda; Stougaard, Jens; Spaink, Herman
Abstract Host pathways mediating changes in immune states elicited by intestinal microbial colonization are incompletely characterized. Here we describe alterations of the host immune state induced by colonization of germ-free zebrafish larvae with an intestinal microbial community or single bacterial species. We show that microbiota-induced changes in intestinal leukocyte subsets and whole-body host gene expression are dependent on the innate immune adaptor genemyd88 . Similar patterns of gene expression are elicited by colonization with conventional microbiome, as well as mono-colonization with two different zebrafish commensal bacterial strains. By studying loss-of-functionmyd88 mutants, we find that colonization suppresses Myd88 at the mRNA level. Tlr2 is essential for microbiota-induced effects onmyd88 transcription and intestinal immune cell composition. It remains unclear how microbial sensing during early-life colonization results in immune homeostasis rather than acute inflammation. Here the authors show that zebrafish larvae colonization suppresses intestinal MyD88, accounting for a considerable proportion of microbiota-induced alterations in immune setpoint.